Vinblastine and Vincristine Production on Madagascar Periwinkle (Catharanthus roseus (L.) G. Don) Callus Culture Treated with Polethylene Glycol - Iskandar, Nisa Nur; Iriawati, (UI Scholars Hub, 2016)
Vinblastine and vincristine are secondary metabolites from Madagascar periwinkles that have a very high economic value as chemotherapy drugs. These compounds are naturally produced in a very low quantity in planta. One promising alternative method for vinblastine and vincristine production is to use a treatment that can trigger plant stress response in vitro. This study has been done to evaluate the effect of drought stress using polyethylene glycol (PEG) on vinblastine and vincristine production in the C. roseus callus culture, which were grown on medium Zenk supplemented with plant growth regulators (PGR) 1 μM NAA + 10 μM Kinetin to induce laticifer and idioblast differentiation. 13-week-old callus cultures were then treated with 0%, 6%, 9%, and 12% (w/v) PEG4000 each for 0, 24, 48, and 72 hours. Biochemical analysis was performed using HPLC to determine the levels of vinblastine and vincristine, while the presence of differentiated cells (idioblasts and laticifers) was determined using a histochemical method. Protein profiles of the culture were determined by SDS-Page. The results showed that drought treatment with PEG4000, until the concentration was 12% (w/v), did not significantly affect the production of vinblastine and vincristine, but might affect terpenoid production. Histochemical analysis confirmed the presence of idioblasts, non-elongated laticifers, and laticifers that were producing and accumulating terpenoids highest in the 12% PEG treatment. PEG treatments also did not change the protein profile of callus.